Ethics and sport - McNamee, M. J. (Mike J.); Parry, S. J. (S. Jim) (Ethics and sport., 1998)
The issues surrounding ethical controversies in sport have filled the media recently. This book by international experts in philosophy and philosophy of sport provides systematic treatment of the ethics of sport from a diverse perspective.